Qualidade de vida e insegurança alimentar em adultos e idosos: estudo Brazuca Natal - Pequeno, Nila Patricia Freire (2020)
Quality of life (QOL) studies have been increasingly valued, given the growing aging population and increased survival of individuals with Chronic Noncommunicable Diseases (NCD). Identifying conditions that may be related to the population's QOL can help explain the heterogeneous distribution of adverse health outcomes, help managers make decisions and expand government actions to ensure better socioeconomic and health conditions for the population. It aimed to analyze socioeconomic, demographic, lifestyle, health, and food security characteristics that may be associated with the QoL of adults and older adults in the city of Natal, Brazil. Cross-sectional research performed using data from the BRAZUCA Natal study. A group of 295 adults and older adults of both sexes aged over 20 years, residents in Natal-Brazil participated in home interviews, using a digital questionnaire (Epicollect5). The WHOQOL-bref questionnaire used to the measured quality of life and the food insecurity by the Brazilian Food Insecurity Scale (EBIA in Portuguese). Also, socioeconomic, demographic, lifestyle, and health data were collected. Statistical analysis included absolute frequency and percentage, and Poisson regression to verify the association between quality of life domains (physical, psychological, social relations and environment) and two general questions “Perception of QOL” and “Satisfaction with health” with the independent variables. Stratified analysis carried out to determine the association between the food security situation and QOL among people with Food security-FS (n=152) and Food Insecurity-FI (n=143). For the general population, be between 40-59 years old (PR=1.70; 95%CI 1.10-2.62), being non-white people (PR=1.55; 95%CI 1.10-2.19) and being mildly insecure (PR=2.76; 95%CI 1.80-4.22) moderate (PR=3.36; 95%CI 2.13-5.32) and severe (PR=3.21; 95%CI 1.83-5.63) were associated with a higher probability of Perception of regular quality of life , bad or very bad, while having mild food insecurity (PR=1.75; 95%CI 1.28-2.39), emotional disorders (PR=1.83; 95%CI 1.39-2.41) and having hypertension (PR=1.34; 95%CI 1.02-1.77) Satisfaction was associated with regular, unsatisfactory or very unsatisfactory health. In the stratified analysis, referring to emotional disorders and sleeping <7 hours a day were associated with low perception of QOL (in different domains), in both groups (FS and FI) (P <0.05). Being overweight and consuming alcoholic beverages ≥ 2 times a week was associated with low perception of QOL in group FI, while having diabetes was associated with low perception of QOL in group FS. In group FI, in addition to the factors mentioned, being elderly, not having a partner, not having daily availability of water, and drinking untreated water was associated with a low perception of QOL, highlighting the social vulnerability of this group. In addition to conditions related to social and health inequities, QOL was shown to be associated with conditions related to physical and mental health, NCD, and their risk factors, regardless of being in a situation of FI. However, in the FI group, the condition was worsened due to the lack of adequate access to water, doubly violating the right to adequate food. Public policies must be conducted to combat inequities, guaranteeing the human right to adequate food, promoting healthy lifestyles and mental health of the population